SKILLS AND ORGANIZATIONS IN IMPROVEMENTS TO DRAWING A BATIK PATTERN OF MICRO, SMALL AND MEDIUM ENTERPRISES WANABATIK PRATAMA LEBAK SUKATANI VILLAGE WANASALAM DISTRICT - Khaeruman Khaeruman; Mira Mira; Sandi Septian; Ghina Alya Fauziyah; Lutfi Yudi Abdilah; Handoko Arya Putra; Lola Lorenza; Lina Marlina; Miuzayyin Arifin; Intan Qurotul Aini (International Journal of Engagement and Empowerment, 2022)
Micro Small and Medium Enterprises Wanabatik Pratama Lebak in Sukatani Village, Wanasalam District, Lebak Regency, is a force to support the area in the village. It considers Batik to be the cultural heritage of the nobility of the Indonesian state, and there is a commitment to preserving the nation's culture. As a result, it is an excellent opportunity to develop MSME Wanabatik Pratama Lebak. Counselling and lectures are the methods used in this service activity. The extension method involves sharing and discussing management information and knowledge. Finally, the evaluation carries out by documenting and observing the implementation of the knowledge conveyed in the commercial activities of Batik artisans. The outcomes of this service activity are in desperate need by managers. At the same time, they provide a positive response to the entrepreneurship programme by emphasizing development services related to the field of entrepreneurship. In addition to bolstering the foundations of entrepreneurialism, this activity also helps business groups improve their operations' administrative management. Commercial and marketing collaboration has begun, as has networked with other parties. This collaboration strengthens the position that leads to community empowerment. The assessment of accounting practises and concepts, as well as organisational management, is quite good.